Relationship between emotional intelligent and job satisfaction among Texas instrument workers - Jamaluddin, Askiah; Arun, G.; Md Jusoh, Zuroni (Australian Academy of Business and Social Sciences, 2014)
The paper explores the relationship between emotional intelligent and job satisfaction among Texas Instrument workers. The emphasis will be on the distribution of respondent in terms of items in emotional intelligent and items in job satisfaction. This involves the explanation about the socioeconomic status of the respondents, the three types of emotional intelligent and job satisfaction. We also discuss the definition and the important of emotional intelligent and job satisfaction in organization. The research location is one of the establish factory in Klang Valley that is Texas Instrument. The result is explained based on the research objectives. The Pearson correlation analysis shows that there are significant relationship between emotional intelligent and job satisfaction among Texas Instrument workers. This paper contribute the information emotional intelligent and job satisfaction for the academicians, organization, and policy makers.